FEATURES OF DIAGNOSIS AND CORRECTION OF IRON DEFICIENCY ANEMIA IN FOOD PROTEIN-INDUCED ENTEROCOLITIS SYNDROME IN INFANTS - Shadrin, O.G.; Marushko, T.L.; Haiduchyk, G.A.; Horianska, M.G. (World of Medicine and Biology, 2020)
The state of iron metabolism in infants with food protein-induced enterocolitis syndrome was determined and the efficacy and safety of ferrous bisglycinate chelate for the correction of iron deficiency anemia in this group of children were studied. 40 children aged 6 months to 3 years with a chronic food protein-induced enterocolitis syndrome were examined. Signs of iron deficiency anemia were found in 80% of children. Administration of ferrous bisglycinate chelate at a dose of 0.5 mg of elemental iron/kg/day for 1 month contributed to the normalization of red blood cells and iron metabolism in the organism, which testified to the high bioavailability and effectiveness of this form of ferrous iron in chronic inflammatory processes in the intestine.
Keywords: infants; food protein-induced enterocolitis syndrome; iron deficiency anemia; ferrous bisglycinate chelate